The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1542/peds.2007-2723
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Pectus Excavatum Markedly Improves Body Image and Perceived Ability for Physical Activity: Multicenter Study

Abstract: Surgical repair of pectus excavatum can significantly improve the body image difficulties and limitations on physical activity experienced by patients. These results should prompt physicians to consider the physiologic and psychological implications of pectus excavatum just as they would any other physical deformity known to have such consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(161 citation statements)
references
References 14 publications
5
145
1
4
Order By: Relevance
“…The methods of assessing pain separately in children 8 to 21 years of age and a parent for the first 30 days post operation have been reported. 2 Patients were followed via phone, mail, or clinical visit at yearly intervals, on or near the anniversary of their surgery, for a period of up to 5 years for complications.…”
Section: Cohort Management and Retentionmentioning
confidence: 99%
“…The methods of assessing pain separately in children 8 to 21 years of age and a parent for the first 30 days post operation have been reported. 2 Patients were followed via phone, mail, or clinical visit at yearly intervals, on or near the anniversary of their surgery, for a period of up to 5 years for complications.…”
Section: Cohort Management and Retentionmentioning
confidence: 99%
“…There is currently no data evaluating the effects of regular psychiatric followup with a psychiatrist on alleviating the psychological burden of poor body image in this patient group. Nevertheless, the lack of correlation between the anatomic severity of the deformity on CT and the physical and body image components of the child psychosocial assessment scores (r = 0.01 and r = 0.06, respectively) observed by Kelly et al suggests that presence of the deformity, regardless of severity, results in body image and psychosocial difficulties worthy of attention [22]. These authors also found that at one year post surgery, patients reported significant reductions in body image concerns (p < 0.0001) and in difficulties in physical functioning (p < 0.0001), and parents perceived significant improvements in their child's emotional functioning (p < 0.01), confirming psychosocial improvements with treatment, independent of the modality employed [22].…”
Section: Indications For the Treatment Of Pectus Deformitymentioning
confidence: 97%
“…Nevertheless, the lack of correlation between the anatomic severity of the deformity on CT and the physical and body image components of the child psychosocial assessment scores (r = 0.01 and r = 0.06, respectively) observed by Kelly et al suggests that presence of the deformity, regardless of severity, results in body image and psychosocial difficulties worthy of attention [22]. These authors also found that at one year post surgery, patients reported significant reductions in body image concerns (p < 0.0001) and in difficulties in physical functioning (p < 0.0001), and parents perceived significant improvements in their child's emotional functioning (p < 0.01), confirming psychosocial improvements with treatment, independent of the modality employed [22]. Similarly, Krasopoulos et al have reported a statistically significant improvement in the self-esteem of pectus deformity patients after having undergone reparative surgery (p = 0.001) [24].…”
Section: Indications For the Treatment Of Pectus Deformitymentioning
confidence: 97%
See 1 more Smart Citation
“…Patients may also increasingly report musculoskeletal complaints, such as back and chest pain, or cardiopulmonary complaints such as dyspnea on exertion and diminished exercise tolerance, which may be related to decreased pulmonary reserve, decreased forced vital capacity, decreased maximal voluntary ventilation, or limitation of cardiac stroke volume (8,9). Furthermore, patients with significant pectus deformities may report palpitations related to mitral valve prolapse, arrhythmias, and atrial & ventricular compression.…”
Section: Brief Report On Thoracic Surgerymentioning
confidence: 99%